Kawasaki disease - a single centre experience - Jovanović, Nikola; Dragana; Vasić, Karin; Hristina (Medicinski časopis, 2025)
Abstract Objective: To compare clinical symptoms, treatment, and outcomes between typical and atypical forms of Kawasaki disease (KD) in patients treated at our institution. Methods: A retrospective observational study was conducted at the Pediatric Clinic, University Clinical Center Niš, reviewing medical records of 17 patients diagnosed with KD between September 2017 and February 2024. Clinical characteristics, laboratory results, treatment regimens, and outcomes were compared between typical (n=12) and atypical KD (n=5) groups. Statistical analysis was performed using the R statistical computing environment. Results: Patients presented with high fever (>38.5 °C) at admission. Diagnosis was delayed in atypical KD cases compared to typical cases (9.6 ± 2.3 days vs. 7.92 ± 2.81 days, respectively). Echocardiographic abnormalities were present in 35% of all cases, including mild left ventricular dysfunction (n=2) and pericardial effusion (n=4). Treatment with intravenous immunoglobulins (IVIg) and aspirin led to significant clinical improvement in most patients. However, corticosteroids were added in 12% (n=2) of cases due to prolonged fever despite initial therapy. One atypical KD patient, diagnosed late, was treated with aspirin alone. Laboratory markers showed notable improvements post-treatment, particularly CRP reduction in typical KD from 77.33 ± 55.92 mg/L to 9.43 ± 7.04 mg/L. Conclusion: Both typical and atypical KD patients showed good short- and medium-term prognoses, with no significant complications noted during follow-up. However, delays in diagnosis, particularly among atypical cases, highlight the need for improved communication across healthcare levels. A larger, multicenter study is recommended to enhance patient management and outcomes. Keywords: vasculitis, pediatric, treatment, laboratory